Geophagus pyrineusi: a new species from the rio Teles Pires, rio Tapajós basin, Brazil (Cichliformes: Cichlidae: Geophagini) - de Carvalho Deprá, Gabriel; Ohara, Willian Massaharu; Silva, Hugmar Pains (Zootaxa, 2022)
Geophagus pyrineusi, new species, is described from the rio Teles Pires drainage, rio Tapajós basin, Brazil. The new species can be diagnosed from the majority of the congeners by presenting a complete infraorbital bar. Additionally, it differs from all other congeners by several coloration-related character states: flank bars 5 and 6–7 as dark as the infraorbital bar, and almost as dark as the midlateral spot; retention of dorsal melanophoric patch 6 as a distinct mark (not connected to any lateral melanophoric patch), and almost as dark as the midlateral spot in adults; retention of lateral melanophoric patch 1p and almost complete absence of dorsal- and caudal-fin color patterns in adults, among other characters.